The Effectiveness of Design Thinking Training in Increasing Intention of Innovative Behavior and Creativity - Hajan Hidajat (Universitas Sebelas Maret, 2019)
This study aims to empirically examine the effectiveness of design thinking training to improve the intention to behave innovatively and creatively. The research method used to carry out this research is the Quasi Experiment Method. The results of hypothesis testing using t-test showed that there was no significant difference in creativity scores between before and after the training treatment. This shows that Design Thinking training is not effective in increasing creativity. However, the two alternative hypotheses were tested using t-test showed that there were significant differences scores of innovative behavior intention before and after treatment of Design Thinking. This shows that Design Thinking training is effective in increasing the intention to behave innovative. This research is expected to contribute studies on the effectiveness of the Design Thinking training method and produce a training module that can be used in the entrepreneurial learning process. Based on the results of this study, Design Thinking training can be used as a method to encourage innovative behavior. intensi berperilaku inovatif, kreativitas, design thinking, pelatihan design thinking